Molecular Evolution of Apolipoprotein Multigene Family and the Original Functional Properties of Serum Apolipoprotein (LAL2) in Lampetra japonica - Han, Qing; Han, Yinglun; Wen, Hongyan; Pang, Yue; Li, Qingwei (Frontiers in Immunology, 2020)
Apolipoprotein (APO) genes represent a large family of genes encoding various binding proteins associated with plasma lipid transport. Due to the long divergence history, it remains to be confirmed whether these genes evolved from a common ancestor through gene duplication and original function, and how this evolution occurred. In this study, based on the phylogenetic tree, sequence alignment, motifs, and evolutionary analysis of gene synteny and collinearity, APOA, APOC, and APOE in higher vertebrates may have a common ancestor, lamprey serum apolipoprotein LAL1 or LAL2, which traces back to 360 million years ago. Moreover, the results of immunofluorescence, immunohistochemistry, and flow cytometry show that LAL2 is primarily distributed in the liver, kidney, and blood leukocytes of lampreys, and specifically localized in the cytoplasm of liver cells and leukocytes, as well as secreted into sera. Surface plasmon resonance technology demonstrates that LAL2 colocalizes to breast adenocarcinoma cells (MCF-7) or chronic myeloid leukemia cells (K562) associated with lamprey immune protein (LIP) and further enhances the killing effect of LIP on tumor cells. In addition, using quantitative real-time PCR (Q-PCR) and western blot methods, we found that the relative mRNA and protein expression of lal2 in lamprey leukocytes and sera increased significantly at different times after stimulating with Staphylococcus aureus, Vibrio anguillarum, and Polyinosinic-polycytidylic acid (Poly I:C). Moreover, LAL2 was found to recognize and bind to gram-positive bacteria (Staphylococcus aureus and Bacillus cereus) and gram-negative bacteria (Escherichia coli) and play an important role in the antibacterial process. All in all, our data reveals a long, complex evolutionary history for apolipoprotein genes under different selection pressures, confirms the immune effect of LAL2 in lamprey sera against pathogens, and lays the foundation for further research regarding biological functions of lamprey immune systems.